2013
DOI: 10.1021/ja4004377
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Nuclear Polarization Enhanced Natural Abundance 17O Spectroscopy

Abstract: We show that natural abundance oxygen-17 NMR of solids could be obtained in minutes at a moderate magnetic field strength by using dynamic nuclear polarization (DNP). Electron spin polarization could be transferred either directly to (17)O spins or indirectly via (1)H spins in inorganic oxides and hydroxides using an oxygen-free solution containing a biradical polarization agent (bTbK). The results open up a powerful method for rapidly acquiring high signal-to-noise ratio solid-state NMR spectra of (17)O nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
144
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(149 citation statements)
references
References 50 publications
3
144
0
2
Order By: Relevance
“…29,40 Indeed, in spite of all of these shortcomings, DNP-enhanced NMR spectroscopy has enabled the measurement of 17 O NMR spectra at natural isotopic abundance. 41,42 For example, DNP-enhanced, natural abundance, 17 O{ 1 H} MAS spectra of inorganic hydroxides were recently obtained in our laboratory, enabling the swift measurements of O−H distances and heteronuclear correlation (HETCOR) spectra. 42 Remarkably, DNP has also enabled us to measure the first 17 O spectra of surface hydroxyl groups in natural-abundance silica ( Figure 4A).…”
Section: Dnp Ssnmr Of Challenging Nucleimentioning
confidence: 99%
“…29,40 Indeed, in spite of all of these shortcomings, DNP-enhanced NMR spectroscopy has enabled the measurement of 17 O NMR spectra at natural isotopic abundance. 41,42 For example, DNP-enhanced, natural abundance, 17 O{ 1 H} MAS spectra of inorganic hydroxides were recently obtained in our laboratory, enabling the swift measurements of O−H distances and heteronuclear correlation (HETCOR) spectra. 42 Remarkably, DNP has also enabled us to measure the first 17 O spectra of surface hydroxyl groups in natural-abundance silica ( Figure 4A).…”
Section: Dnp Ssnmr Of Challenging Nucleimentioning
confidence: 99%
“…However, the situation changes when one is using an organic-solvent-based DNP matrix, such as those already used for a variety of studies [29][30][31][32][33][34][35][36], and/or quadrupolar nuclei [31,[35][36][37][38]. Organic solvents are chosen based on a few criteria: their inertness to the analyte and polarizing agent, the position of their resonances in NMR spectra, their RT vapor pressure, and their physical state at experimental temperatures [39].…”
Section: Obtaining An Enhanced Absolute Sensitivitymentioning
confidence: 99%
“…It is important for both industrial (metal oxides) and health (biomolecules) sectors but its low natural abundance ( $ 0.04%), quadrupolar nature (spin-5/2), and low gyromagnetic ratio (γ 17O o1/7 γ 1H ) limit its applicability. Nevertheless, recent studies have shown promise for these two vital sectors with work on inorganic oxides and hydroxides [31] and biologically-relevant small molecules [6] with both direct [6,31] and indirect (via 1 H) [31] MAS-DNP. Since quadrupolar parameters are very sensitive to the local environment, and the low temperatures currently required for efficient DNP have been shown to be exceptionally beneficial to studies of quadrupolar spins [36], as well as low-γ [67] nuclei, it can be envisaged that MAS-DNP has a very appropriate direction.…”
Section: Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of Dynamic Nuclear Polarization (DNP), using gyrotron microwave (MW) sources, combined with MAS has opened the door to many advanced studies of solids at high magnetic fields [1]. The development and implementation of high field gyrotrons up to the Terahertz range has enabled the construction of high field MAS-DNP instruments, and led to the commercialization of MAS-DNP spectrometers by Bruker Inc. [2] operating up to 18 T. Theses high field DNP instrument developments have triggered a vast interest of the solid-state NMR community in MAS-DNP experiments, both for biological [3][4][5][6][7][8][9][10][11] and material science [12][13][14][15][16][17][18][19][20][21][22] applications. Most of these experiments performed today are using nitroxide based bi-radicals such as TOTAPOL [23,24,2,8,25,26,9], and recently new nitroxide based biradicals have been introduced with varying longitudinal relaxation times, phase memory times (or transverse relaxation time), electron-electron dipolar couplings, and relative gÀtensor orientations such as AMUPOL, bCTbK, or TEKPOL [27,26,28].…”
Section: Introductionmentioning
confidence: 99%